Treatment Patterns and FLT3 Mutation Testing Among Patients with Acute Myeloid Leukemia in China: A Retrospective Observational Study - Cheng LJ; Gong B; Young CH; Krishnan P; Wang Y; Wei H; Zhou C; Wei S; Li Y; Fang Q; Zhong J; Wu EQ; et al. (Dove Medical Press, 2024)
Li-Jen Cheng,1 Benfa Gong,2 Christopher H Young,3 Prabhuram Krishnan,1 Ying Wang,2 Hui Wei,2 Chunlin Zhou,2 Shuning Wei,2 Yan Li,2 Qiuyun Fang,2 Jia Zhong,4 Eric Q Wu,5 Yingchang Mi,2 Jianxiang Wang2 1Medical Affairs, Astellas Pharma Singapore Pte. Ltd., Singapore; 2Institute of Hematology & Blood Diseases Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Tianjin, People's Republic of China; 3Advanced Informatics & Analytics, Astellas Pharma US Inc., Northbrook, IL, USA; 4Analysis Group, Inc., Beijing, People's Republic of China; 5Analysis Group, Inc., Boston, MA, USACorrespondence: Jianxiang Wang, State Key Laboratory of Experimental Hematology, National Clinical Research Center for Blood Diseases, Institute of Hematology & Blood Diseases Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Tianjin, 300020, People's Republic of China, Tel +86 13821389157, Email wangjx@ihcams.ac.cnIntroduction: For acute myeloid leukemia (AML), prognosis is particularly poor in patients harboring FMS-like tyrosine kinase 3 (FLT3) gene mutations, though routine screening for these mutations at diagnosis has been shown to be insufficient. The understanding of the impact of FLT3 mutations on treatment decisions is limited.Methods: In this retrospective, observational study, we investigated the key epidemiological characteristics, treatment patterns and responses among adult patients with newly diagnosed (ND) AML in China, who initiated treatment from January 1, 2015, to December 31, 2019, or progressed to relapsed/refractory (R/R) AML by December 31, 2020.Results: Of the 853 ND AML patients included, 63.4% were screened for FLT3 status, and 20.1% tested positive (FLT3MUT) at initial diagnosis. Of 289 patients who progressed to R/R AML during the study period, 24.9% were screened at the diagnosis of R/R AML, and 19.4% tested positive; 20.5% of screened patients changed FLT3 status at first diagnosis of R/R AML. Initial treatment regimens or treatment responses did not seem to differ in patients with ND AML by FLT3 mutation status. In patients with R/R AML, there was an apparent difference in second-line treatment choices by FLT3 mutation status; however, the number of FLT3-mutated patients were limited to demonstrate any meaningful distinction. FLT3-mutated R/R AML was associated with shorter relapse time.Conclusion: Study findings showed that there was a lack of routine testing for FLT3 mutations at first diagnosis of R/R AML, and initial treatment decisions did not differ by FLT3 mutation status. Given the clinical burden of FLT3MUT, likelihood of FLT3 status changes, and emerging FLT3 inhibitors, further routine FLT3 screening is needed to optimize treatment of R/R AML. Keywords: acute myeloid leukemia, epidemiology, real-world, retrospective study